Double ionization of He by ion impact: Second-order contributions to the fully differential cross section - López, Sebastián David (2014)
In this work, we present a second-order Born series treatment for the double ionization of He by ion impact. In particular, we show that the well-known independent events and independent electron models naturally result from an on-shell treatment for the second-order Born approximation. A transition amplitude which coherently includes first- and second-order terms in the projectile interaction is introduced to study the role of the two-step-1, shake-off, and two-step-2 mechanisms at different impact energies. Fully differential cross sections for proton and antiproton impact are presented and analyzed for different projectile momentum transfers. © 2014 American Physical Society.